A Show for Two - Bhuiyan, Tashie (Toronto, Ontario, Canada : Inkyard Press, 2022)
Determined to win the student film competition, Mina makes a deal with indie film star Emmitt Ramos, and as they spend time together and NYC starts to feel more like home than ever before, she wonders if winning is worth losing everything.
new ya book 2025 spring.
Keywords: Bangladeshi Americans -- Fiction; Motion pictures -- Production and direction -- Fiction; Contests -- Fiction; Own voice; High schools -- Fiction; High school seniors -- Fiction; New York (N.Y.) -- Fiction; Young adult fiction; Realistic fiction